The utility of universal urinary drug screening in chronic pain management. Issue 1 (1st January 2018) - Wiseman, Luke K.; Lynch, Mary E.
ABSTRACT: Background: A recent systematic review found few studies that assessed the value of urinary drug screening (UDS) in the management of chronic pain. The Pain Management Unit in Halifax, Nova Scotia, has recently implemented tandem mass spectrometry (TMS) UDS for all new patients. Aims: To study the prevalence of unexpected TMS UDS results at a hospital-based chronic pain center, to assess which drugs are most likely to contribute to an unexpected result and to assess the clinical utilization of unexpected results by pain physicians. Methods: From June 2014 to June 2016, a total of 664 patients with chronic non-cancer pain (CNCP) were seen for initial consult. Charts were reviewed and used to create a database containing sex, age, UDS result, physician, and medication/illicit drug history. For all unexpected UDS results, an interview was conducted with the treating physician to determine its clinical implications. Results: For the general pain specialists, the overall percentage of patients with an unexpected UDS result was 16.67%. Excluding codeine, at most 4.47% of patients tested unexpectedly positive for a strong opioid. Although eight out of nine physicians found UDS helpful in general, only 29.58% of unexpected results were helpful in the management of their patients and directly influenced their care. Conclusions: The prevalence of an unexpected UDS result in patients with CNCP is significant. Most physicians agree that UDS is helpful but in only a limited number of cases did the unexpected result provide helpful information that significantly influenced patient care.